An Examination on the Effect of Prior Knowledge, Personal Goals, and Incentive in an Online Employee Training Program. Issue 4 (29th November 2017) - Zha, Shenghua; Adams, Andrea Harpine; Calcagno‐Roach, Jamie Marie; Stringham, David A.
Abstract: This study explored factors that predicted learners' transformative learning in an online employee training program in a higher education institution in the U.S. A multivariate multiple regression analysis was conducted with a sample of 74 adult learners on their learning of a new learning management system. Four types of participants' behaviors were measured and aligned with 3 phases of transformative learning, namely, number of active visits in Phase 1, alignment of personal goals with actual actions in Phase 1, number of posted messages in Phase 4, and program completion in Phase 6. Results showed that prior knowledge was the strongest predictor of the early stages of transformative learning. Financial incentive had an effect on participants' Phase 1 of transformative learning. No significance was observed regarding the impact of personal goals. Implications and suggestions on providing and improving technology online training to employees were discussed in the end of this article for practitioners and researchers.